The Ability of Large Language Models to Generate Patient Information Materials for Retinopathy of Prematurity: Evaluation of Readability, Accuracy, and Comprehensiveness - Sevinç Arzu Postacı; Ali Dal (Türk Oftalmoloji Dergisi)
Objectives: This study compared the readability of patient education materials from the Turkish Ophthalmological Association (TOA) retinopathy of prematurity (ROP) guidelines with those generated by large language models (LLMs). The ability of GPT-4.0, GPT-4o mini, and Gemini to produce patient education materials was evaluated in terms of accuracy and comprehensiveness. Materials and Methods: Thirty questions from the TOA ROP guidelines were posed to GPT-4.0, GPT-4o mini, and Gemini. Their responses were then reformulated using the prompts “Can you revise this text to be understandable at a 6th-grade reading level?” (P1 format) and “Can you make this text easier to understand?” (P2 format). The readability of the TOA ROP guidelines and the LLM-generated responses was analyzed using the Ateşman and Bezirci-Yılmaz formulas. Additionally, ROP specialists evaluated the comprehensiveness and accuracy of the responses. Results: The TOA brochure was found to have a reading level above the 6th-grade level recommended in the literature. Materials generated by GPT-4.0 and Gemini had significantly greater readability than the TOA brochure (p<0.05). Adjustments made in the P1 and P2 formats improved readability for GPT-4.0, while no significant change was observed for GPT-4o mini and Gemini. GPT-4.0 had the highest scores for accuracy and comprehensiveness, while Gemini had the lowest. Conclusion: GPT-4.0 appeared to have greater potential for generating more readable, accurate, and comprehensive patient education materials. However, when integrating LLMs into the healthcare field, regional medical differences and the accuracy of the provided information must be carefully assessed.